1993
DOI: 10.1111/j.1365-2265.1993.tb00341.x
|View full text |Cite
|
Sign up to set email alerts
|

The desmopressin stimulation test in the differential diagnosis of Cushing's syndrome

Abstract: Desmopressin was able to stimulate the pituitary-adrenal axis in patients with Cushing's disease and, like corticotrophin releasing hormone, it may prove useful in the differential diagnosis of Cushing's syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
105
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(116 citation statements)
references
References 24 publications
6
105
2
3
Order By: Relevance
“…DST and CRH tests are well known for the diagnosis of Cushing's disease [3,5]. ACTH release would be caused by an abnormal increase in vasopressin type 1b receptors in response to a vasopressin type 2 receptor agonist, DDAVP, on pituitary corticotroph adenoma cells [6], and has been used for the differential diagnosis of ACTH-dependent Cushing's syndrome [7]. Nevertheless, the data in Cushing's disease has been known to overlap with some cases of EAS [2].…”
Section: Low-dose Dexamethasone Suppression Test (Dst)mentioning
confidence: 99%
See 1 more Smart Citation
“…DST and CRH tests are well known for the diagnosis of Cushing's disease [3,5]. ACTH release would be caused by an abnormal increase in vasopressin type 1b receptors in response to a vasopressin type 2 receptor agonist, DDAVP, on pituitary corticotroph adenoma cells [6], and has been used for the differential diagnosis of ACTH-dependent Cushing's syndrome [7]. Nevertheless, the data in Cushing's disease has been known to overlap with some cases of EAS [2].…”
Section: Low-dose Dexamethasone Suppression Test (Dst)mentioning
confidence: 99%
“…The DDAVP test has been used for the diagnosis and differential diagnosis of ACTH-dependent Cushing's syndrome from pseudo-Cushing's syndrome; plasma ACTH levels were increased in a response to DDAVP in Cushing's disease, but classically, there was a slight response in normal or EAS cases [7]. We previously reported that the DDAVP test was useful for discriminating Cushing's disease from normal subjects when more than a 1.5-fold increase in the ACTH level compared with the basal level was defined a significant response [6].…”
Section: Bmentioning
confidence: 99%
“…corticotropin-releasing hormone (CrH) test are well defined for the diagnosis of Cushing's syndrome [4][5][6], while desmopressin has been used for the differential diagnosis of ACTH-dependent Cushing's syndrome [7,8]. However, it is clear that the diagnosis and differential diagnosis of Cushing's syndrome are still challenging problems in clinical endocrinology [9,10].…”
mentioning
confidence: 99%
“…Desmopressin has been used for the differential diagnosis of ACTH-dependent Cushing's syndrome since 1993 (87). Moreover, it has also been studied with the aim of differentiating Cushing's syndrome from states of pseudo-Cushing's (88).…”
Section: Desmopressin Testmentioning
confidence: 99%
“…The desmopressin test has been used for the differential diagnosis of ACTH-dependent Cushing's syndrome since 1993 (87). Subsequently, several studies have shown a response in the majority of patients with CD (~80%) (1).…”
Section: Desmopressin Testmentioning
confidence: 99%